The reality and the standard in the stays of irish ERASMUS students: “… no entendí nada. Ahora, estoy acostumbrado a esta desesperación de LA «S»” - Fuentes González, Antonio Daniel (Universidade Estadual Paulista, 2020)
This study analyses some sociolinguistic accounts by Irish ERASMUS students at the University of Almería (Spain). It shows the need and suitability of a more plural and varied methodological perspective based upon biographical and linguistic approaches. This is intended to foster a teaching panorama that grants a higher regard to multilingualism, as it result as a crucial experience for  a higher linguistic command in ELE (Spanish as a foreign language) and in general any LE (foreign Language)  or L2[u1]  (Second Language).